Arrhythmia Detection Using Convolutional Neural Models - Torres Ruiz, Jorge; Buldain Pérez, Julio David; Beltrán Blázquez, José Ramón (Jornada de Jóvenes Investigadores del I3A, 2019)
Our main goal was studying the effectiveness of transfer learning using 2D CNNs. For this task, we generated spectrograms from ECG segments that were fed to a CNN to automatically extract features. These features are classified by a MLP into arrhythmic or normal rhythm segments, achieving 90% accuracy.